Poverty accounting by factor components: With an empirical illustration using chinese data - Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The purpose of this paper is to develop two poverty decomposition frameworks and to illustrate their applicability. A given level of poverty is broadly decomposed into an overall inequality component and an overall endowment component in terms of income or consumption determinants or input factors. These components are further decomposed into finer components associated with individual inputs. Also, a change in poverty is decomposed into components attributable to the growth and redistributions of factor inputs. An empirical illustration using Chinese data highlights the importance of factor redistributions in determining poverty levels and poverty changes in rural China.
Keywords: I32; D33; C43; 330; poverty decomposition; factor components; inequality; Shapley value; China; Armut; Dekompositionsverfahren; China; Shapley-Wert